The Ultrastructure of the Corpus Luteum of the Goat - Azmi, T. I.; Bongso, T. A. (1985)
The ultra structure of luteal cells and the proportion of the different cell types in the functional corpus luteum of the goat were studied using the electron microscope. Two luteal cell types, large and small, were present in the corpus luteum of this species. The large more rounded luteal cell possessed numerous mitochondria and electron dense membrane- bound granules, extensive agranular endoplasmic reticulum and granular endoplasmic reticulum which at times appeared as stacks of closely packed cisternae. Few lipid droplets were present iri the luteal cell cytoplasma while whorled agranular endoplasmic reticulum was absent. Interspersed amongst the large luteal cells were smaller luteal cells with tapering cytoplasmic processes. These cells differed from the large luteal cells in that they possessed fewer mitochondria and electron dense membrane- bound granules. Occasional nuclei of the small luteal cells contained cytoplasmic inclusion bodies.